Dworkin’s Alternative to Berlin’s Value Pluralism - Noreikaitė, Aistė; Jokubaitis, Alvydas (Problemos, 2015)
The aim of this paper is to prove that Ronald Dworkin’s value monism is a reasonable alternative to Isaiah Berlin’s value pluralism. Berlin criticized monism for the reduction of diversity of value, its tendency to dogmatism and links with totalitarianism. Dworkin rejects Berlin’s conception of monism and argues for a much more moderate conception of monism. This paper examines Dworkin’s critique for pluralism. While opposing to the exponents of Berlin’s pluralism (A. Plaw, J. Allenas, J. Gray, M. Minow and J. W. Singer), it argues that Dworkin’s moderate value monism allows us to give a better account of values than pluralism. The paper defends the position of value monism, which is most often strictly criticized in contemporary discourse of moral and political philosophy.